Application of low-pressure reverse osmosis membrane for Zn2+ and Cu2+ removal from wastewater - Ujang, Zaini; Anderson, G. K. (Elsevier Science B.V., Amsterdam, 1996)
Reverse osmosis (RO) is a pressure-driven operation which normally requires more than 690 kPa (100 psig) for effective removal of metal ions from their solvents. This paper, however, illustrates the feasibility of using complexation and low-pressure RO membranes for the removal of Zn2+ and Cu2+ by applying pressures significantly below 690 kPa. The results show that the use of EDTA is a reliable method for increasing the percentage removal of both Zn2+ and Cu2+ with sulphonated polysulphone RO membranes. The percentage removal of metal ions of Zn2+ was slightly greater than that for Cu2+